Desmoplastic Small Round Cell Tumour of Childhood: A Report of Four Cases Demonstrating Wider Clinical Features and Variable Outcome. (1997) - Ray, Ruma; Traunecker, Heidi C. L.; Raafat, Faro; Stevens, Michael C. G.
Abstract : Purpose . Four further cases of desmoplastic small round cell tumour with multi phenotypic differentiation are described. Subjects . Two patients were typical (male, adolescent with peritoneal tumour and, in one case, liver metastases) and did not respond well to treatment. Two other patients showed less usual features (young, female with retroperitoneal disease, both with intraspinal extension and renal tract obstruction). Both responded favourably to multi-modal treatment regimens including extensive and invasive supportive care. Results . Histologically, all tumours showed clear features of this diagnosis, namely angulated nests of small cells in a background of fibrovascular stroma. Immunohistochemistry typically showed divergent differentiation with neural, muscle and epithelial marker positivity. All four tumours stained positive for the Wilms' tumour 1 suppressor gene product. Electron microscopy showed intercellular tight junctions, cytoplasmatic intermediate filaments and absence of microvilli. Rare neurosecretory-type granules were observed. Discussion . These cases illustrate a broader spectrum of clinical presentation than previously associated with this diagnosis.